Strategic and Integrated Management of Islamic Education Foundations for Institutional Sustainability - Dino Dino; Muhammad Fazis; Suharmon Suharmon (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
The growing role of foundations as governing bodies of Islamic education has become increasingly strategic, particularly for those managing multiple institutions with rapid expansion. This dynamic context generates managerial complexity, especially in human resource development and infrastructure provision. This study aims to analyze how Islamic education foundations in West Sumatra implement the core management functions of planning, organizing, actuating, and controlling. Employing a qualitative field research approach, data were collected through in-depth interviews, direct observation, and document analysis involving foundation executives, divisional heads, and school leaders. Data analysis followed a descriptive qualitative framework, encompassing reduction, presentation, and conclusion drawing. The findings reveal that foundation management is conducted in a structured and centralized manner, characterized by strategic and medium-term orientation. Human resource and infrastructure planning is integrated into a five-year strategic plan aligned with financial management. Organizational structuring is achieved through functional divisions with clear task distribution and authority. Implementation is carried out selectively and progressively, utilizing internal resources and foundation-based management information systems. Control mechanisms include periodic evaluation, budget adjustments, asset documentation, and cross-divisional coordination. The study implies that strategic and integrated management practices strengthen institutional sustainability, offering a replicable model for large-scale Islamic education governance in diverse contexts.